Inside Cover: Simulating Pump–Probe Photoelectron and Absorption Spectroscopy on the Attosecond Timescale with Time‐Dependent Density Functional Theory (ChemPhysChem 7/2013). Issue 7 (29th April 2013) - De Giovannini, Umberto; Brunetto, Gustavo; Castro, Alberto; Walkenhorst, Jessica; Rubio, Angel
<x xml:space="preserve">Abstract</x> The time evolution of the π–π* transition in an ethylene molecule is modelled with ab initio energy‐ and angle‐resolved photoelectron spectroscopy calculations, presented on p. 1363 by U. De Giovannini, A. Castro, A. Rubio et al.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>